Um sistema para o controle de gastos com a frota de veículos da prefeitura municipal de Lajes/RN - Silva, Rauan Hiago da (Universidade Federal Rural do Semi-Árido, 2020)
In city halls, due to the lack of easy-to-use computerized systems for controlling debt spending, many managers choose to manually control debt spending. In addition to the laborious work that this type of control requires, there are issues regarding data recovery and storage, as well as accountability and transparency in public websites. With that in mind, a solution for cost control system was created to mitigate those problems. In this work, a system to assists the mayor’s office in controlling the expenses, storage and recovery of the public data in the Municipality of Lajes/RN.
Monografia
Keywords: Transparência; SCGC; Sistema; Públicos; Armazenamento; recuperação; Transparency; SCGC; System; Public; Storage; recovery; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO